The mystery of cognitive structure and how we can detect it: Tracking the development of cognitive structures over time - Ifenthaler, Dirk; Masduki, I.; Seel, N. (Springer, 2011)
Many research studies have clearly demonstrated the importance of cognitive structures as the building blocks of meaningful learning and retention of instructional materials. Identifying the learners' cognitive structures will help instructors to organize materials, identify knowledge gaps, and relate new materials to existing slots or anchors within the learners' cognitive structures. The purpose of our empirical investigation is to track the development of cognitive structures over time. Accordingly, we demonstrate how various indicators derived from graph theory can be used for a precise description and analysis of cognitive structures. Our results revealed several patterns that helped us to better understand the construction and development of cognitive structures over time. We conclude by identifying applications of our approach for learning and instruction and proposing possibilities for the further development of our approach. © 2009 Springer Science+Business Media B.V.